2021
DOI: 10.1200/jco.2021.39.3_suppl.102
|View full text |Cite
|
Sign up to set email alerts
|

Minimal residual disease (MRD) detection with circulating tumor DNA (ctDNA) from personalized assays in stage II-III colorectal cancer patients in a U.K. multicenter prospective study (TRACC).

Abstract: 102 Background: Numerous studies have shown the clinical utility of ctDNA, a non-invasive biomarker to detect MRD and stratify CRC patients who are more likely to relapse. We present an analysis of MRD detection in CRC patients from a prospective multicentre UK study, who were monitored pre- and post-surgery before adjuvant chemotherapy (ACT). Methods: The study recruited patients diagnosed with stage II-III CRC (n=122), including a subset of rectal patients who underwent tri-modality treatment (TMT). All pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 0 publications
0
29
0
Order By: Relevance
“…Of the positive patients, 42.9% (6/14) eventually relapsed while only 8.6% (8/93) of the negative patients relapsed (HR: 10; 95% CI: 3.3-30; p < 0.001). In multivariate analysis, ctDNA status was the most significant prognostic factor associated with relapse-free survival (HR: 28.8, 95% CI: 3.5-234.1; p < 0.001) [79]. Similarly, in patients undergoing surgery for peritoneal metastases, high levels of pre-operative ctDNA and new postoperative ctDNA alterations in the context of preoperative alterations predicted worse outcomes [59].…”
Section: Ctdna To Measure Residual Diseasementioning
confidence: 98%
“…Of the positive patients, 42.9% (6/14) eventually relapsed while only 8.6% (8/93) of the negative patients relapsed (HR: 10; 95% CI: 3.3-30; p < 0.001). In multivariate analysis, ctDNA status was the most significant prognostic factor associated with relapse-free survival (HR: 28.8, 95% CI: 3.5-234.1; p < 0.001) [79]. Similarly, in patients undergoing surgery for peritoneal metastases, high levels of pre-operative ctDNA and new postoperative ctDNA alterations in the context of preoperative alterations predicted worse outcomes [59].…”
Section: Ctdna To Measure Residual Diseasementioning
confidence: 98%
“…Reliable MRD diagnosis is employed to predict relapse, risk classification, treatment selection and guide risk-adapted adjuvant immune therapy. Data from multicentre prospective studies in other tumours such as colon [9] and breast cancer [123] have shown that precision medicine largely relies on MRD. An appropriate drug dose is administered to patients through MRD detection, therefore preventing the drug's adverse effects.…”
Section: Challenges and Future Prospective Of Liquid Mrdmentioning
confidence: 99%
“…MRD refers to the cells that persist after therapy and are resistant to conventional therapy. Several studies have proven that MRD can be a prognostic factor for relapse in these patients [9]. MRD is well established in malignancies of the haematological and lymphoid organs.…”
Section: Introductionmentioning
confidence: 99%
“…In metastatic colorectal cancer (mCRC), KRAS , NRAS , and BRAF assessment is mandatory for treatment selection and prognostication, as RAS mutations confer resistance to anti-EGFR antibodies and BRAF V600 mutations indicate poor prognosis. NGS testing for extended RAS and BRAF gene mutations is currently standard practice, and ctDNA testing using single gene assays (PCR-based) has been shown to be an effective alternative to tissue-based genotyping and is approved by the European Medicines Agency (Idylla TM ctKRAS, Idylla TM ctNRAS-BRAF, OncoBEAM TM RAS) but remains to be incorporated into clinical guidelines [ 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ]. Although tumor tissue in patients with metastatic CRC is often easier to obtain than in lung cancer patients, the benefits of fast turnaround time with plasma ctDNA ddPCR testing may confer a benefit to patients needing to start treatment sooner.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…Moving forward, in early-stage colorectal cancer (CRC), there is compelling evidence demonstrating the role of ctDNA detection after curative-intent therapy as an important prognostic factor [ 73 ]. This approach, known as minimal residual disease (MRD) detection, represents an opportunity to better select patients that may benefit from more intense adjuvant therapy, or those that do not need further chemotherapy, with the aim of improving survival rates and minimizing toxicity and unneeded therapy [ 74 ].…”
Section: Colorectal Cancermentioning
confidence: 99%